Penelitian penggunaan minarex sebagai bahan pelunak dalam pembuatan kompon karet sol karet cetak - Kasmudjiastuti, Emiliana; Murwati, Murwati (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1995)
The objective of this research is to use Minarex oil as a softener in making rubber sole compound and to know the optimal of formulation. The research applied Minarex type 3 with four kinds of A, B, C, D and with variation 5 parts, 6 parts, and 7 parts. Data analysed using Statistic Method with Compleetely Randomized Design and Split Plot Design. The result of this study showed that all kind of Minarex oils could be used to softener in making rubber sole compound and fullfilled the spesification of SNI 0778-89-A,